2022
DOI: 10.3390/agriculture13010075
|View full text |Cite
|
Sign up to set email alerts
|

Quality Profile of Several Monofloral Romanian Honeys

Abstract: The objective of this research was to evaluate some quality-defining physicochemical parameters (moisture, specific gravity, pH, free acidity, ash, electrical conductivity, total phenols, and total flavonoids content, K, Ca, Mg, Na, and P) of seven Romanian monofloral honeys (linden, acacia, rapeseed, sunflower, mint, raspberry, and chestnut) collected in 2017. The investigated quality parameters are mainly within the recommended limits set by standards for honey. Sample analyses indicate the presence of antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The color of multifloral honey samples varied from 14.5 mm Pfund (white) to 69.7 mm Pfund (light amber) in both areas I and II (Tables 2 and 3). Much research found different colors of the same type of honey: color varied from 0.1 mm Pfund in Romanian acacia honey [38] to 20.0 mm Pfund in Serbian acacia honey [35]; Bodor et al 2021 [36] noted large differences in the color of the Hungarian samples within the same botanical group (linden), from 38.27 mm Pfund to 139.48 mm Pfund. For monofloral honey, in general, it is known that acacia honey is light-colored and chestnut honey is dark-colored; for polyflora honey, the color is given by a large number of pollen types.…”
Section: Physicochemical Determinationsmentioning
confidence: 99%
“…The color of multifloral honey samples varied from 14.5 mm Pfund (white) to 69.7 mm Pfund (light amber) in both areas I and II (Tables 2 and 3). Much research found different colors of the same type of honey: color varied from 0.1 mm Pfund in Romanian acacia honey [38] to 20.0 mm Pfund in Serbian acacia honey [35]; Bodor et al 2021 [36] noted large differences in the color of the Hungarian samples within the same botanical group (linden), from 38.27 mm Pfund to 139.48 mm Pfund. For monofloral honey, in general, it is known that acacia honey is light-colored and chestnut honey is dark-colored; for polyflora honey, the color is given by a large number of pollen types.…”
Section: Physicochemical Determinationsmentioning
confidence: 99%
“…• is higher than reports of Ethiopian [54] and Serbian honey [21]; • could be considered the same-but with higher means-as Estonian [55], Yemenian [56], Moroccan [57], Argentinian [58], Brazilian, and Portuguese honey [59]; • could be considered the same-but with lower means-as Polish [60][61][62], Slovenian flower [63], Hungarian linden [64], Romanian linden [65], Bulgarian linden [66], Italian [67], Malaysian [68], and New Zealand honey [69];…”
Section: Polyfloral Honey Element Chemical Profilementioning
confidence: 77%
“…• could be considered the same-but with lower means-as Polish [60][61][62], Slovenian flower [63], Hungarian linden [64], Romanian linden [65], Bulgarian linden [66], Italian [67], Malaysian [68], and New Zealand honey [69];…”
Section: Polyfloral Honey Element Chemical Profilementioning
confidence: 99%
“…Thus, Pop I.M. et al [21] evaluated 7 monofloral honey varieties (linden, acacia, rapeseed, sunflower, mint, raspberry and chestnut) from a physicalchemical point of view (moisture, specific gravity, pH, free acidity, ash, electrical conductivity, total phenols and total flavonoid content, K, Ca, Mg, Na and P). The quality parameters that were investigated fell within the recommended limits established by the regulated standards.…”
mentioning
confidence: 99%